Corporate Governance, Firm Characteristics and Audit Quality: Evidence from Thai Listed Companies - ศรีจั่นเพชร ศิลปพร; ภักดี อนุวัฒน์ (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2019)
This paper examines the impact of corporate governance mechanisms and organization characteristics on audit quality. Secondary data was collected from annual registration statements (Form 56-1) and financial statements. The samples included 1,188 firm-year observations of Thai listed Companies from 2015 to 2017. Descriptive statistics and a binary logistic regression were used to analyze the data and test the hypothesis. Corporate governance variables were composed of board size, foreign board, board independence, board education, and audit committee size. Firm characteristics variables consisted of firm size, debt ratio, and firm profitability. In this research, the audit firms big 4 were used as the audit quality. The results revealed that foreign board, board education, firm size, and firm profitability have positive effects on audit quality. On the other hand, the evidence shows that board independence and audit committee size have negative effects on audit quality. All in all, the results suggest that corporate governance mechanisms are important for a firm’s audit quality.